Development Electronic Student Worksheet based on Relating, Experiencing, Applying, Cooperating, and Transferring (REACT) in Introduction to Chemistry and Laboratory - Yusup Maulana; Imas Eva Wijayanti; Solfarina Solfarina (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2021)
This research aims to development a REACT-based e-worksheet that is feasible to use to stimulate the critical thinking, creativity, collaboration, communication (4C) skills and determine student response. The challenges of a dynamic era require students to have a 4C skills set critical thinking and problem-solving skills; creativity and innovation; communication; and collaboration. One of the tools that can be used in online learning to achieve this goal is to use the electronic Student Worksheet (E-Worksheet) which includes the student's 4C skill values with REACT strategies: Relating, Experiencing, Applying, Cooperating, and Transferring. The research chooses one of the topics in chemistry, which is introduction to chemistry and laboratories. This REACT-based e-worksheet was developed using the ADDIE development model which consists of five stages those are analysis, design, development, implementation, and evaluation. In addition, the study used a sample of 10 students of mathematic and natural science 12th grade MAN 4 Tangerang. Based on the results of validation and student response questionnaires, REACT-based e-worksheet to stimulate students' 4C skills was declared valid and obtained an average percentage of 91.8% with very good criteria.